√(b2−a2)(s2−x2)
√(b2−a2)(s2×2)
√x2−a2−b2s
x2−a2−b2s
√(b2x2)(a2−s2x2)
Correct answer is E
s = √(a2x2−b2y2)
s2 = a2x2−b2y2
b2y2 = a2x2 - s2
b2y2 = a2−s2x2x2
1y2 = (a2−s2x2x2)×1b2
1y2 = a2−s2x2b2x2
∴ y^2 = \frac{b^2 x^2}{a^2 - s^2 x^2}
y = \sqrt{\frac{b^2 x^2}{a^2 - s^2 x^2}}
Find the mid point of S(-5, 4) and T(-3, -2) ...
Use the graph of sin (θ) above to estimate the value of θ when sin (θ) = -0.6 for ...
A regular polygon of n sides has 160o as the size of each interior angle. Find n...
If sin 30° = 0.5, what is the cosine of its complement?...
Two distinct sectors in the same circle substend 100° and 30° respectively at the centre of ...
Solve the equation 2a^2 - 3a - 27 = 0...
The angle of elevation of an aircraft from a point K on the horizontal ground 30\alpha. If the a...
If y \alpha \frac{1}{x^2} and y = 1\frac{1}{4} when x = 4, find the value of y when \(x = \f...